The Effect of Promotional Brochure Quality on Tourism Promotion in North Nias Regency - Afore Tahir Harefa; Nurmawati Harefa; Yulidartini Larosa; Ica Murni Tafonao (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of tourism promotion brochure quality on tourism promotion in North Nias Regency. A quantitative approach with a causal research design was employed using a survey method. The respondents consisted of 50 individuals who had read or been exposed to official tourism promotion brochures and were selected through purposive sampling. Data were collected using a structured questionnaire measured on a five-point Likert scale and analyzed through simple linear regression. The results show that the quality of tourism promotion brochures has a positive and statistically significant effect on tourism promotion (β = 0.812; p < 0.05). The coefficient of determination (R²) of 0.681 indicates that brochure quality contributes substantially to tourism promotion, while the remaining variance is influenced by other factors beyond the scope of this study. These findings suggest that printed tourism brochures continue to play an important role in shaping tourists’ perceptions and interest. This study provides empirical support for destination marketing theory and emphasizes the importance of brochure quality in regional tourism promotion strategies.